The Influence of Socio-Economic Factors and Farmer Participation in Institutional Capital on Farmers' Participation in the National Community Empowerment Program - Fatahullah, Fatahullah; Shifwatun Aqiilah, Hana (International Journal of Agriculture System, 2024)
Community empowerment programs aim to empower farmers by providing them access to the resources, training, technology, and support needed to increase agricultural productivity, increase income, and achieve agricultural desires. However, the success of such programs highly depends on the active participation of farmers. Factors influencing farmer participation in the NCEP program were analyzed using a binary logistic regression approach using STATA (Statistics and Data). Several factors are thought to influence farmer participation in the NCEP program, namely age, education level, income level, community meetings, participation in cooperatives, and participation in savings and loans. The results of the analysis show that what is influential at the 1% error level are the variables education, community meetings, and participation in savings and loans. Meanwhile, the influence at the 5% error level is the cooperative variable. Further efforts are needed regarding outreach to farmers who have not participated in the program and the government is expected to create a special strategy to attract farmers' interest in joining and participating in the Community Empowerment National Program (NCEP), so that farmer welfare and productivity can be achieved. In addition, it is suggested that cooperatives and savings and loans actively provide easy access to information and capital as well as increase their activities to support farmers in implementing the NCEP program.